Energy Optimization of Methanol Production using CO₂ from Natural Gas Sweetening via Reactor Heat Recovery, Compressor Integration, and Cooling Water Reuse - Farrel Dzakwan Alghiffary; Jaguar Mulia Perdana; Theona Melinda Thomson; Dania Alya Karima; Alma Camila Nathania; Renny Gustiara Rahim; Cahya Kamila Ramadhani Putri (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Methanol production via CO₂ hydrogenation is an efficient alternative for supporting energy sustainability and reducing carbon emissions; however, conventional processes still face limitations in energy efficiency and resource utilization. This study aims to optimize the methanol production process through the integration of heat recovery, compressor energy utilization, and water recycling. Simulations were conducted using Aspen HYSYS by comparing baseline process conditions with modified process conditions under the same operating conditions. The results show that integrating heat from the reactor effluent and the cooling unit reduces external energy requirements, while the water recycling system successfully reduces fresh water usage by up to 100%. Additionally, heating energy requirements decreased by 27.21%, and compressor energy needs were fully met through internal energy recovery. From an economic perspective, significant operational cost savings were achieved, particularly in steam consumption, without compromising product quality, as methanol purity remained at 97.91%. Overall, the integration of mass and energy in this process has proven capable of improving efficiency, reducing costs, and supporting the sustainability of CO₂-based methanol production. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).